Beyond beans: Women entrepreneurs are transforming communities in Eastern Congo - Awotide, Bola Amoke; Kalisya, Lucky; Njingulula, Paulin; Ntamwinja, Julie; Mulonda, Lydie; Kajunju, Napoleon; Birachi, Eliud; Nchanji, Eileen; Rubyogo, Jean Claude (2024)
The Beans for Women Empowerment Project is helping women plant seeds of change in their communities. A recent visit by the Canadian ambassador recognized the benefits of investing in womens’ empowerment.